PEMBELAJARAN MENULIS TEKS EKSPLANASI KOMPLEKS DENGAN MENGGUNAKAN METODE PICTURE AND PICTURE - Ira Nailil Haq; Neng Irma; Indra Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The background of this study is based on the fact that students feel difficult when writing explanatory texts. The difficulties faced by students include difficult to express ideas in writing complex explanatory texts. This statement is proven by the answers of the students when filling out the questionnaire given by the teacher. This study aims to see the effect of the picture and picture method on the results of student writing. The researcher used an experimental method with a design (one group pre-test post-test), the data collected was the initial test (pre-test) and the final test (post-test). The instruments used were evaluation questions, to see the results of student writing, observations to see the learning process of students in the class, and questionnaires to find out student responses related to the application of the methods carried out on 30 class students as a research sample. The results of the study show that the picture and picture learning method influences student learning outcomes in writing complex explanatory texts. It can be seen from the average value obtained by students before and after being treated using the picture and picture method. The average value of students before being given treatment is 74.2 and after being given treatment using the method of picture and picture the average value of students increases to 82.7. So, the picture and pictured method can be applied in learning to write explanatory texts because it is proven to increase the average value of students in writing complex explanatory texts.